Price-based Measurement of Financial Globalization: A Cross-Country Study of Interest Rate Parity - Ito, Hiro; Chinn, Menzie D. (My University, 2007)
The authors characterize the relationship between ex post exchange rate depreciation and the interest differential for a set of countries that spans developed and emerging market economies. The measured ex post uncovered interest differentials in terms of both levels and absolute values are then related to measures of trade and financial openness, financial development, government budget balances, institutional development, and exchange rate regimes. They find wide diversity in the coefficient relating depreciations and interest differentials.